2013
DOI: 10.4314/ajtcam.v11i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the anti-inflammatory, analgesic and antipyrexic activities of betulinic acid derived from <i>Tetracera Potatoria</i>.

Abstract: Background: The anti-inflammatory and anti-nociceptive activity of betulinic acid (BA) was investigated in this study. The triterpene was isolated from the ethyl acetate extract of Tetracera potatoria and its structure was verified by IR and NMR spectroscopy. The bioactivity of this compound was assessed using carrageenan-induced paw oedema in rats and carrageenan-induced pulmonary oedema in mice for the antiinflammatory activity, while acetic acid-induced writhing test in mice and zymosan-induced fever in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
(13 reference statements)
0
17
0
1
Order By: Relevance
“…Thereafter, BA (Sigma-Aldrich) and metformin (as a standard type 2 diabetes drug; Sigma-Aldrich) were orally administered by stainless steel feeding tubes (24 gauge [0.6 mm outer diameter×0.4 mm inner diameter]×25 mm) for 2 weeks after confirmed diabetes induction in the treatment groups. Hence, mice were divided into 6 groups (n=10): control, diabetes, diabetes+BA at 10 mg/kg, 20 mg/kg, and 40 mg/kg [11], and diabetes+metformin at 200 mg/kg [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, BA (Sigma-Aldrich) and metformin (as a standard type 2 diabetes drug; Sigma-Aldrich) were orally administered by stainless steel feeding tubes (24 gauge [0.6 mm outer diameter×0.4 mm inner diameter]×25 mm) for 2 weeks after confirmed diabetes induction in the treatment groups. Hence, mice were divided into 6 groups (n=10): control, diabetes, diabetes+BA at 10 mg/kg, 20 mg/kg, and 40 mg/kg [11], and diabetes+metformin at 200 mg/kg [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Since, it has been suggested that the development of diabetic nephropathy would be started at 3 weeks after STZ injection (2); BA (Sigma-Aldrich, USA) and metformin (Sigma-Aldrich, USA) were orally administered 2 weeks after confirmed diabetes induction for prevention of diabetic nephropathy. Hence, mice were divided into six groups (10 mice in each group): control, diabetes group, diabetic mice receiving BA (10, 20 and 40 mg/kg) (10), and diabetic mice receiving metformin (200 mg/kg) (11) as a standard diabetes drug. …”
Section: Methodsmentioning
confidence: 99%
“…Betulinic acid has been reported from both Sonneratia apetala [ 73 ] and Ceriops tagal [ 75 ]. Anti-inflammatory, analgesic, and antipyrexic effects of this compound isolated from Tetracera potatoria have been reported [ 76 ]. Inhibition of cyclooxygenase-2 (COX-2) activity (which can result in analgesic and anti-inflammatory effects through inhibition of prostaglandin biosynthesis) has been reported for bruguierin A, isolated from Bruguiera gymnorrhiza [ 60 ].…”
Section: Pharmacological Activities Of Heritiera Fomes mentioning
confidence: 99%